Information Systems Of Ticketing Bus By Online Based On Web On PO Sinar Jaya - Hendro Muftadi; Rini Malfiany (LPPM STMIK Rosma, 2018)
PO Sinar Jaya is one of transportation provider companies that still develop and not yet using internet technology as services development to customers, the problem is they can’t see the schedule total remainder ticket directly, and company can’t give direct information to the customer. Systems development methods used is waterfall, waterfall consists of some stage the flow of activity that walked in one direction from the start to finish system develop project, start from analysis, design, code, trial, and supporting stage. According to observation that be held in PO Sinar Jaya Cibitung obtained complete information about procedure order the ticket during the time, so can give the solution to information system planning order ticket bus by online. With the information ordering ticket bus using online system expected can help ordering ticket bus activities and can to increase sale volume, increase the service quality and company’s image.